PERAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN DAERAH ISTIMEWA YOGYAKARTA (ANALISIS INPUT-OUTPUT DAERAH ISTIMEWA YOGYAKARTA UNTUK KOMODITAS TEBU) - SURYANTINI, ANY; HARTONO, SLAMET; NURHAYATI, AZIZATUN; WIDYANINGSIH, WIWIN (Jurnal Social Economic of Agriculture, 2015)
Local economic development is held by focusing on the leading sectors. One of measures of the success of economic development viewed from the economic growth by measuring income and GDP. A sector which gives the high contribution to others sectors, increasing income, and GDP is included  as contributive sector.The aim of the study is to analyze the contribution of agriculture sectors especially the sugarcane  in increasing economic growth of Yogyakarta. The analyze is based on input-output data from Badan Pusat Statistik Yogykarta in year 1995, 2000, and 2010.The result of the research is that the sugarcane is not the leading sector of Yogykarta. In the other side, rank of sugarcane in output multiplier, income multiplier, and GDP’s multiplier in 2010 and its contribution in economic growth are better than 1995 and 2000. It means, by the better management on agriculture, in the future, the sugarcane can increase the economic growth of  Yogyakarta. Keywords: tebu, analisis input-output, pengganda output, pengganda pendapatan, pengganda nilai